Role of neuronal integrity in maintaining gut functions and homeostasis - Chauhan, Vipin; Advised by Nongthomba, Upendra (Bangalore : Indian Institute of Science, 2024)
This thesis investigates two main aspects of neuronal integrity and gut health. Firstly, it examines the intricate relationship between neuronal integrity and the maintenance of gut homeostasis in Drosophila melanogaster. Secondly, it investigates the potential association of gut dysbiosis with prevalent neurodegenerative diseases like Alzheimer's disease (AD), Parkinson's disease (PD), Multiple sclerosis (MS), and Amyotrophic lateral sclerosis (ALS). For understanding the role of neuronal integrity in maintenance of gut health and homeostasis, we have chosen various neuronal, muscle and neuro-muscular mutants of Drosophila melanogaster. We showed that these flies with impaired neuronal signaling exhibit early mortality, increased intestinal permeability, and deformed septate junction complexes (Ssk-Mesh) accompanied by structural defects in the intestinal muscles. We also observed fewer intestinal stem cells (ISCs), leading to a reduced regenerative capacity of the posterior midgut in these flies. Furthermore, the downregulation of the damage induced ISC proliferation pathway through Upd3 was identified. These results highlight the critical role of neuronal signaling in maintaining gut homeostasis through ISC proliferation in the Drosophila posterior midgut. We have also shown the positive role of a traditional ayurvedic medicine known as Shankhjira in ameliorating the gut defects in flies with impaired neuronal signaling. Shankhjira improved the pool of ISCs in the posterior midgut of neuronal mutant flies exhibiting defective regenerative capacity. Hence, Shankhjira can be considered as potential therapeutic medicine for treating gut abnormalities. Next, to investigate the role of gut dysbiosis in neurodegenerative diseases, this study conducts a comparative in-silico analysis of gut microbiome across AD, PD, MS, and ALS. This analysis highlights the similarities and differences in microbial dysbiosis signatures among these diseases. Specific changes in microbial phyla populations, such as the increase in Bacteroidetes, Actinobacteria, Proteobacteria, and Firmicutes, and decrease in Bacteroidetes and Firmicutes. Functional insights suggest potential metabolic connections of dysbiotic microbes to the altered microbiome-gut-brain axis in these diseases. For instance, the microbes with elevated populations lack pathways for synthesising SCFA, butyrate, and Propionate. Also, these microbes have a high capacity for producing L-glutamate, an excitatory neurotransmitter. On the other hand, Tryptophan, a precursor for serotonin and other neuroactive molecules (Quinolinate, kynurenine, IAA, indole, IPA, and tryptamine), has a lower representation in the annotated genome of elevated microbes. Similarly, histamine, a crucial neuro-immuno-modulatory compound, was less expressed in the genome of microbes present in elevated conditions in neurodegenerative diseases. Finally, the neuroprotective compound spermidine was also less represented in the genome of elevated microbes. Together, our study shows the potential metabolic involvement of dysbiotic microbes in neurodegenerative diseases. In summary, this thesis sheds light on the intricate interplay between neuronal signaling and gut homeostasis. Simultaneously, it shows the potential metabolic implications of dysbiotic microbes in major neurodegenerative diseases. These findings hold promise for future research directions and potential therapeutic strategies leveraging microbiome-based approaches in addressing neurodegenerative conditions like AD, PD, MS, and ALS. The insights garnered from this thesis provide evidence that gut can be considered a future therapeutic target in case of neurological diseases.
Includes references.
PhD;2024.Developmental Biology and Genetics.
Keywords: Gut-brain axis; Gut microbiota; Drosophila melanogaster